New genera of Talitridae in the revised Superfamily Talitroidea Bulycheva 1957 (Crustacea, Amphipoda, Senticaudata) - Lowry, J.k.; Myers, A.a. (Zootaxa, 2019)
Thirty seven new talitrid genera are described: Albidiator gen. nov.; Amphiatlantica gen. nov.; Asiaorchestia gen. nov.; Bulychevia gen. nov.; Calviator gen. nov.; Canariorchestia gen. nov.; Chevreuxiana gen. nov.; Dallwitzia gen. nov.; Defeo gen. nov.; Dendrorchestia gen. nov.; Derzhavinia gen. nov.; Dracorchestia gen. nov.; Fleuria gen. nov.; Galaporchestia gen. nov.; Hermaniator gen. nov.; Houlia gen. nov.; Hurleyella gen. nov.; Ignamborchestia gen. nov.; Indiorchestia gen. nov.; Insulariator gen. nov.; Kaalorchestia gen. nov.; Kellyduncania gen. nov.; Laniporchestia gen. nov.; Laurenia gen. nov.; Leslieorchestia gen. nov.; Lutruwitiator gen. nov.; Morinoia gen. nov.; Oamaru gen. nov.; Omaiorchestia gen. nov.; Opunorchestia gen. nov.; Pickorchestia gen. nov.; Sinbadorchestia gen. nov.; Snaresorchestia gen. nov.; Speziorchestia gen. nov.; Swaziator gen. nov.; Tasmanella gen. nov.; and Wairua gen. nov. The superfamily Hyaloidea Bulycheva 1957 stat. nov. is established. Caribitroides Bousfield, 1984, Dana Lowry, 2011, Makawe Duncan, 1994, Mexitroides Lindeman, 1990, Parorchestia Stebbing, 1899, Puhuruhuru Duncan, 1994 and Waematau Duncan, 1994 are re-diagnosed and Mexitroides Lindeman, 1990 is raised to generic level. Type material of Tethorchestia antillensis Bousfield, 1984 is illustrated for the first time.